Functional Characterization of Arylalkylamine N-Acetyltransferase, a Pivotal Gene in Antioxidant Melatonin Biosynthesis from Chlamydomonas reinhardtii - Ok-Jin Hwang; Kyoungwhan Back (MDPI AG, 2022)
Arylalkylamine N-acetyltransferase (AANAT) is a pivotal enzyme in melatonin biosynthesis that catalyzes the conversion of serotonin to N-acetylserotonin. Homologs of animal AANAT genes are present in animals, but not in plants. An AANAT homolog was found in Chlamydomonas reinhardtii, but not other green algae. The characteristics of C. reinhardtii AANAT (CrAANAT) are unclear. Here, full-length CrAANAT was chemically synthesized and expressed in Escherichia coli. Recombinant CrAANAT exhibited AANAT activity with a Km of 247 μM and Vmax of 325 pmol/min/mg protein with serotonin as the substrate. CrAANAT was localized to the cytoplasm in tobacco leaf cells. Transgenic rice plants overexpressing CrAANAT (CrAANAT-OE) exhibited increased melatonin production. CrAANAT-OE plants showed a longer seed length and larger second leaf angle than wild-type plants, indicative of the involvement of brassinosteroids (BRs). As expected, BR biosynthesis- and signaling-related genes such as D2, DWARF4, DWARF11, and BZR1 were upregulated in CrAANAT-OE plants. Therefore, an increased endogenous melatonin level by ectopic overexpression of CrAANAT seems to be closely associated with BR biosynthesis, thereby influencing seed size.